European National Society Cardiovascular Journals - Background, rationale and mission statement of the “Editors´ Club" - Alfonso, Fernando; Ambrosio, Giuseppe; Pinto, Fausto J.; van der Wall, Ernst E. (SA Heart Journal, 2017)
Cardiovascular scientific production in Europe is growing both in quantity and in quality. Promoting high-quality research is a major goal of the European Society of Cardiology (ESC). The ESC has two highly respected official general journals, namely the European Heart Journal and Cardiovascular Research, devoted to clinical and basic research respectively. The ESC also publishes several sub-speciality official journals covering the full spectrum of cardiovascular diseases and related techniques. Most European countries, however, also have their own cardiovascular journals. National Society Cardiovascular Journals (NSCJ) are time-honoured and classically disseminate high-quality scientific research mainly originating from each particular European country. They also play a major role in education and harmonisation of clinical practice. Most NSCJ are published in local languages but many of them also incorporate English editions. Altogether, NSCJ provide a highly effective means to disseminate cardiovascular research produced in Europe. Scientific knowledge, however, has no barriers and many of these journals have gained an undisputed international profile. Some NSCJ, however, are just emerging and would benefit from networking support. It became clear that enhancing collaboration among NSCJ Editors would facilitate advancement in knowledge and further diffusion of scientific and educative contents. Developing a “Constitution Document” and “Mission Statement” was considered desirable to set the basis of future collaboration among NSCJ Editors. We assumed this responsibility in recognising the crucial role of NSCJ in Europe. Our target was to produce and issue a core document with fundamental principles upon which all NSCJ Editors would agree. Common goals will be identified and agreed-on measures will be pursued. The constitution document presented herein was therefore developed to formalise the NSCJ Editors´ Club Task Force.